The Effect Of Sleep Hygiene On Sleep Disorders For The Elderly In Pangudi Luhur Pangudi Luhur Integrated Original Center Bekasi - Mara Imbang Satriawan Hasiolan; Wada, Fauziah H (PT. Nursing Genius Care, 2025)
Background: Sleep hygiene is the most effective non - pharmacological therapy as wrong one simple behavior _ from a number of factor environment individual and as wrong one tool help healthy sleep . _ sleep hygiene is wrong one great therapy _ easy , cheap and comprehensive that can used for repair disturbance sleep elderly Purpose: Research _ this aim for knowing Influence Sleep Hygiene To Disturbance Sleep Elderly , Analyze disorders sleep elderly before given intervention Sleep Hygiene in Orphanage , Analyzing disturbance sleep after given intervention Sleep Hygiene Elderly in the orphanage Methods: Design study this use method quantitative descriptive Quasy Experiment Pre test - Post test with control group . Results: The results showed that on group intervention mean value before conducted intervention sleep hygiene is 3.88 and average value after conducted intervention sleep hygiene is 8.48 which means there is enhancement mean value before and after given intervention sleep hygiene. Group mean _ control before i.e. 3,42 and average value after ie 3.76. so that no there is significant difference _ Among score disturbance sleep before and after on group control , can concluded that on group control that doesn't accept intervention and only conducted care standard just no there is change on score disturbance sleep . Conclusion: Application sleep hygiene by regular effective in increase good sleep and could resolve disturbance sleep on various population group age elderly.